PanaxGDB: A Comprehensive Platform for Panax - Lin, Yuan; Hao, Bing; Lu, Ying Chun; Dong, Yang; Li, Ying; Zhang, Guang Hui; Yang, Zi Jiang; Xiang, Gui Sheng; Liu, Guan Ze; Li, Xue Jiao; Zhu, Qin; Yang, Qing Hui; et al. (Frontiers in Plant Science, 2022)
The Panax genus, a valuable natural medicinal source in worldwide abundant triterpenoid saponins that presents extensive pharmacological activities. In the past decades, increasing numbers of scientists employed molecular biotechnology and breeding technique to generate omics data and cultivars information mainly from P. ginseng (ginseng), P. quinquefolium (American ginseng) and P. notoginseng (Sanqi) for synthetic biology, quality improvement and cost-control cultivation. Meanwhile, with lots of data produced, there has been concerns that redundant data generation might occur and relatively scattered data may slip, with a large number of scientists desired for a reliable comprehensive omics database of Panax genus for time saving and integrated analysis. To provide all-inclusive reliable and valuable information for researchers. An open comprehensive database with integrated omics data and varieties information of Panax genus was established. The database contains nearly 600 compounds information from 12 Panax species, the draft genomic sequence with annotations and expression levels, single nucleotide polymorphisms, GWAS analysis (genome-wide association analysis) based on agronomic traits, globally collected germplasm information, summarization, omics data of Panax genus and online versatile analytic tools. The construction of database of the Panax genus will be updated when new data released and sustain serving as a central portal to boost the research of the biology and functions of Panax genus. PanaxGDB is available at PanaxGDB, http://panaxGDB.ynau.edu.cn.